The Evolution of the Meaning of “Dūsh” in the Thoughts of Khayyam, Sanai, and Hafez - Ali Mohammad Moazzeni; Ameneh Rajabi (مطالعات زبانی و بلاغی)
Khayyam, Sanai, and Hafez are three great poets and thinkers with different philosophical orientations. Although all the three poets are deeply rooted in Iranian Islamic culture, they have also been influenced by the pre-Islamic Iranian culture and Zoroastrian tradition. The effect of both Zoroastrian and Islamic cultures has often led to penumbras of meaning of same words over the centuries. One of those words is the term “Dūsh”, which traditionally meant “last night” and occasionally synonymous with “dawn” until the time of Khayyam and Sanai. We can view “Dūsh” from two perspectives. Firstly, the well-regarded status of “night” from the perspectives of Zoroastrianism and Islam, and secondly, the connection between “night” or “dawn” with the time of drinking wine and the morning wine (“sabūhi”). Both before and after Khayyam and Sanai, “night” and “dawn” have had an inseparable link with celestial hidden messages. In the verses of Ferdowsi, Manuchehri, and Naser Khosrow, we can vividly observe the connection between "night"/"dawn" and nocturnal inspirations. Sometimes these inspirations are conveyed by hidden messengers such as "Sorūsh" – the celestial messenger angel in Zoroastrianism – and at other times, "night" alone serves as the carrier of secrets and mysteries. The connection of “Sorūsh” with “night” is also reflected in Islam through “revelation” and “Gabriel” which set the groundwork for the divine perspective on “night”, “last night” and the “presence of the hidden messenger” in the poetry of later centuries specially, in Hafez’ poems. Before the genesis of this perspective, “Dūsh” undergoes its first semantic transformation in Khayyam’s Rubayiat, distancing itself from the divine concept associated with “Sorūsh” and Zoroastrian beliefs. Later, with the appearance of mysticism and Sanai’s poetry, it once again rediscovers its divine essence. In the light of the concept of “love,” it obtains a new meaning. Finally, in The Ghazals of Hafez, in which all former concepts and ideas are evolved and reach their pinnacle, the concept “Dūsh” becomes the central theme of his thought, especially by the addition of the meaning of “eternal” to this concept.